'We are like orphans': exploring narratives of Lao doctoral alumni educated in Sweden. Issue 3 (3rd May 2016) - Silfver, Ann-Louise; Berge, Britt-Marie
ABSTRACT: In this article, we explore the narratives of 10 doctoral alumni from Lao People's Democratic Republic (PDR) who underwent graduate training in Sweden. The narratives identify challenges encountered by the alumni but more importantly reveal the agency by which these challenges were overcome. The most important strategy was that of collaborative learning, actively enlisting the help of other doctoral students and supervisors, thus challenging the prevalent discourse about doctoral studies as an individual endeavour. Inspired by post-colonial perspectives, the article reveals juxtapositions between Lao colonial experiences and Swedish ignorance of their ramifications. The article argues that programmes in Sweden should work more actively towards a collaborative and inclusive learning process. This strategy becomes especially important when doctoral endeavours involve participants from both the global south and the global north, and it could be an important step in challenging the hegemonic position of the global north in processes of knowledge production.